2013
DOI: 10.1074/jbc.m113.477984
|View full text |Cite
|
Sign up to set email alerts
|

Prefoldin Protects Neuronal Cells from Polyglutamine Toxicity by Preventing Aggregation Formation

Abstract: Background: Prefoldin, a molecular chaperone composed of six subunits, prevents misfolding of newly synthesized nascent polypeptides. Results: Prefoldin inhibited aggregation of pathogenic Huntingtin and subsequent cell death. Conclusion: Prefoldin suppressed Huntingtin aggregation at the small oligomer stage. Significance: Prefoldin plays a role in preventing protein aggregation in Huntington disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 54 publications
2
52
0
Order By: Relevance
“…Since the prefoldin complex contains two -type subunits (PFD3 and PFD5) and four -type subunits (PFD1, PFD2, PFD4 and PFD6), siRNAs targeting PFD5 (-type subunit) and PFD2 (-type subunit) were chosen for knockdown. As previously reported (Miyazawa et al, 2011;Tashiro et al, 2013;Abe et al, 2013), knockdown of either PFD2 or PFD5 reduced the expression levels of other prefoldin subunits (Fig. 3A) and knockdown of PFD2 and PFD5 disrupted the prefoldin complex detected by a glycerol density gradient centrifugation (data not shown).…”
Section: Stimulation Of -Synuclein Aggregation and Cell Death In Presupporting
confidence: 60%
See 2 more Smart Citations
“…Since the prefoldin complex contains two -type subunits (PFD3 and PFD5) and four -type subunits (PFD1, PFD2, PFD4 and PFD6), siRNAs targeting PFD5 (-type subunit) and PFD2 (-type subunit) were chosen for knockdown. As previously reported (Miyazawa et al, 2011;Tashiro et al, 2013;Abe et al, 2013), knockdown of either PFD2 or PFD5 reduced the expression levels of other prefoldin subunits (Fig. 3A) and knockdown of PFD2 and PFD5 disrupted the prefoldin complex detected by a glycerol density gradient centrifugation (data not shown).…”
Section: Stimulation Of -Synuclein Aggregation and Cell Death In Presupporting
confidence: 60%
“…Indeed, we have shown that prefoldin inhibits formation of pathogenic Huntingtin oligomers that are larger than a dimer and trimer (Tashiro et al, 2013). Alternatively, it is also possible that the effects of prefoldin knockdown on synuclein aggregation and toxicity are indirect, perhaps through the accumulation of unrelated misfolded nascent proteins that then compromise the overall folding capacity of the cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockdown of MM-1/PFD5 resulted in disruption of the prefoldin complex and loss of protective activity against oligomer formation of pathogenic Huntingtin and α-synuclein. [37][38][39] Prefoldin also modulates aggregation of Amyloid-β (Aβ). 40,41) Furthermore, mice possessing a missense mutation in MM-1α at amino acid number 110 from leucine to arginine (L110R) exhibit various symptoms, including degeneration of the cerebellum and retina and male infertility.…”
Section: Tumor Suppressor Mm-1 and Neurodegenerationmentioning
confidence: 99%
“…However, they exhibit properties that potentially lead to enhanced cellular toxicity or poor CNS bioavailability (10 -14). Similarly, endogenous chaperones have been shown to inhibit polyQ-Htt aggregation also without affecting total polyQ-Htt protein levels (15)(16)(17). Recently, overexpression of the endogenous protein, negative regulator of ubiquitin-like protein 1 (NUB1), decreased mt-Htt protein accumulation and rescued toxicity via activation of proteasomal degradation of mt-Htt in both in vitro and in vivo models (18).…”
mentioning
confidence: 99%